At the heart of freedom : feminism, sex, and equality - Cornell, Drucilla (Princeton, N.J. : Princeton University Press, 1998)
Cornell begins by discussing what she believes lies at the heart of freedom: the ability for all individuals to pursue happiness in their own way, especially in matters of love and sex. This is only possible, she argues, if we protect the "imaginary domain"--a psychic and moral space in which individuals can explore their own sources of happiness. She writes that equality with men does not offer such protection, in part because men themselves are not fully free. Instead, women must focus on ensuring that individuals face minimal interference from the state and from oppressive cultural norms. They must also respect some controversial individual choices. Cornell argues in favor of permitting same-sex couples to marry and adopt children, for example. She presses for access to abortion and for universal day care. She also justifies lifestyles that have not always been supported by other feminists, ranging from staying at home as a primary caregiver to engaging in prostitution. She argues that men should have similar freedoms--thus returning feminism to its promise that freedom for women would mean freedom for all.
Includes bibliographical references (p. 233-243) and index.
Keywords: Feminism; Women's rights; feminismi; miehen asema; naisen asema; naiset; naistutkimus; tasa-arvo.; feminism; mannens ställning; kvinnans ställning; kvinnor; kvinnoforskning; jämställdhet